Birds of prey : new crime stories - Box, C. J.; Gerritsen, Tess; Reichs, Kathy; Atkins, Ace; Cosby, S. A.; Ryan, Hank Phillippi; Dugoni, Robert; Brennan, Allison; Hurwitz, Gregg; Armstrong, Kelley (Mysterious Press, 2026)
Eleven twisty, scary, surprising, and imaginative stories writtenbased on the following writing prompt: Write a story inspired by a bird of prey. The result? An egg worth more than its weight in gold.A mysterious operative known as Owl. An eagle-watcher who sees morethan just eagles. And a story that places the Maltese Falcon in...anursing home?